Effects of growth hormone in patients with chronic renal failure: experience in children and adults - Wühl, Elke; Schaefer, Franz (Hormone research, 2002)
Recombinant human growth hormone (GH) has proven effective in promoting growth in short children with chronic renal failure before and after renal transplantation. The action of GH and its mediator insulin-like growth factor 1 on body composition, protein, glucose and bone metabolism offers additional therapeutic options. One might be the improvement of the catabolic state in adults with end-stage renal failure. In few pilot studies and two placebo-controlled studies of 6 months duration, GH treatment in adults on dialysis showed clear anabolic effects resulting in a significant increase in lean body mass.
Published online: November 17, 2004
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 12.01.2021